Falkland/Malvinas: una questione ancora aperta - Passadelimi, Alessandro Maria (Rivista di studi politici internazionali, 2010)
The sovereignty dispute between Argentina and United Kingdom about the Falkland (Malvinas) Islands, lasting since the British occupation in 1833, has came up again when the British Government decided to start the exploitation of hydrocarbons. Although the solidarity expressed to both parts from the respective Southern American and European partners, the conflict cannot be solved on a multilateral base. Due to the sensitiveness of Argentinean public opinion on the subject, it would be desirable a first step from the British side to reactivate the dialogue suddenly interrupted by the Argentinean dictatorship with the military attempt to recover the territory in 1982, but also a reconsideration of the issue in Argentina. La querelle territoriale entre Argentine et Royaume-Uni sur les Îles Falkland/Malvines, qui remonte à l’occupation britannique en 1833, est devenue de nouveau actuelle lorsque le Gouvernement britannique a décidé de commencer l’exploitation d’hydrocarbures. Malgré la solidarité manifestée à chaque part par les respectifs partenaires sudamericains et européens, le conflit ne peut pas être résolu sur une base multilatérale. À cause de la sensibilité de l’opinion publique argentine en matière, ça serait souhaitable un premier pas britannique au fin de rouvrir le dialogue brusquement interrompu par la dictature argentine avec la tentative militaire pour récupérer l’archipel en 1982, mais aussi une reconsidération de la question en Argentine. PAROLE CHIAVE: Argentina; Regno Unito; Controversia territoriale; Idrocarburi; Atlantico meridionale.